Plan de comercialización de productos derivados de la caña de azúcar (panela y cócteles) de la Empresa Ávila S.A. de la parroquia Ramón Campaña, cantón Pangua, provincia de Cotopaxi, año 2018. - Ávila Suquillo, Ángela Alexandra (2019)
The objective of this project is to develop a marketing plan for products derived from sugar cane (panela and cocktails) produced by the company Ávila S.A. in Ramón Campaña village, Pangua county, Cotopaxi province. Descriptive and quantitative research were used, with the use of the survey technique applied to the Quevedo population, where the following results could be known: the main opportunity was the production of sugar cane in the Ramón Campaña village and the production of panela which is a healthy product that can replace the consumption of sugar in the population of Quevedo; the company must formalize the company with its due sanitary registration of the panela and cocktails, as a strategy to capture the market of the city of Quevedo: the target market for panela and cocktails identified that Ávila S.A., hoping to capture a demand of 57.235 pounds, as well as a demand for 332.772 liters of cocktail; the penetration of the product is proposed through marketing channels such as supermarkets, grocery stores and markets; the budget of the marketing proposal indicated that the total investment amounts to $ 154.203.93, where the fixed investment represents 45% and the operating costs represent 55%. In conclusion, the project is viable because an Internal Rate of Return of 27% was obtained, which is higher than the discount rate that is 12%. In relation to the Net Present Value, an amount of $ 65.117, obtaining a recovery period of two years and eigth months, which evidenced the feasibility of the investment made.